Differential Hippocampal Expression of BDNF Isoforms and Their Receptors Under Diverse Configurations of the Serotonergic System in a Mice Model of Increased Neuronal Survival - Foltran, Rocío Beatriz; Stefani, Karen Melany; Bonafina, Antonela; Resasco, Agustina; Diaz, Silvina Laura (Frontiers in Cellular Neuroscience, 2019)
Neurotrophic factors are relevant regulators of the neurogenic process at different levels. In particular, the brain-derived neurotrophic factor, BDNF, is highly expressed in the hippocampus (HC) of rodents and participates in the control of neuronal proliferation and survival in the dentate gyrus. Likewise, serotonin is also involved in the regulation of neurogenesis, though its role is apparently more complex. Indeed, both enhancement of serotonin neurotransmission as well as serotonin depletion, paradoxically increase neuronal survival in the HC of mice. In this study, we analyzed the expression of the BDNF isoforms, i.e. pro- and mature-BDNF, and their respective receptors p75 and TrkB, in the HC of mice chronically treated with para-chloro-phenyl-alanine (PCPA), an inhibitor of serotonin synthesis. The same analysis was conducted in hyposerotonergic mice with concomitant administration of the 5-HT1A receptor agonist, 8-Hydroxy-2-(di-n- propylamino)tetralin (8-OH-DPAT). Increased expression of p75 receptor with decreased expression of pro-BDNF was observed after chronic PCPA. Seven-day treatment with 8-OH-DPAT reestablished the expression of pro-BDNF modified by PCPA, and induced an increase in the expression of p75 receptor. It has been demonstrated that PCPA-treated mice have higher number of immature neurons in the HC. Given that immature neurons participate in the pattern separation process, the object pattern separation test was conducted. A better performance of hyposerotonergic mice was not confirmed in this assay. Altogether, our results show that molecules in the BDNF signaling pathway are differentially expressed under diverse configurations of the serotonergic system, allowing for fine-tuning of the neurogenic process.